Cassava production marketing and utilization in Meghalaya, India: results of a value chain assessment. - Kharlyngdoh, A.; Anantharaman, M.; Shanpru, E.; Naziri, D. (International Potato Center, 2018)
The scoping study of RTCs in Meghalaya led by FoodSTART+ and LAMP in 2016 recommended conducting a cassava value chain study in key cassava producing areas in Meghalaya to strengthen the value chain and increase benefits to farmers. This study was conducted in September-October 2017 with the overall objective of identifying major constraints in cassava production, marketing and use, and opportunities for interventions that could significantly increase returns for farmers and processors; specifically studying all aspects of cassava value chain in Meghalaya. These pieces of information will be used to plan LAMP/MBDA activities in the cassava sub-sector. This study followed a value chain analysis approach and involved a cross-sectional data collection among a range of stakeholders and value chain actors through review of secondary data, key informant interviews, focus group discussions, and surveys. The study was conducted in the main cassava producing districts of East Garo, West Garo, and West Khasi hills as well other important markets dealing with cassava including Shillong.